Integrating Cross-case Analyses and Process Tracing in Set-Theoretic Research: Strategies and Parameters of Debate. (January 2018) - Beach, Derek; Rohlfing, Ingo
In recent years, there has been increasing interest in the combination of two methods on the basis of set theory. In our introduction and this special issue, we focus on two variants of cross-case set-theoretic methods— qualitative comparative analysis (QCA) and typological theory (TT)—and their combination with process tracing (PT). Our goal is to broaden and deepen set-theoretic empirical research and equip scholars with guidance on how to implement it in multimethod research (MMR). At first glance, set-theoretic cross-case methods and PT seem to be highly compatible when causal relationships are conceptualized in terms of set theory. However, multiple issues have not so far been thoroughly addressed. Our article builds on the emerging MMR literature and seeks to enhance it in four ways. First, we offer a comprehensive and coherent elaboration of the two sequences in which case studies can be combined with a cross-case method. Second, we expand the perspective and discuss QCA and TT as two alternative methods for the cross-case analysis. Third, based on the idea of analytical priority, we introduce the distinction between a condition-centered and a mechanism-centered variant of set-theoretic MMR. Fourth, we point attention to the challenges of theorizing and analyzing arrangements of conditions and mechanisms associated with sufficient conjunctions.